Method for generating non-circular gear with addendum modification and its application in transplanting mechanism - Zhou, Maile; Yang, Yuchao; Wei, Mingxu; Yin, Daqing (International Journal of Agricultural and Biological Engineering, 2020)
With a focus on the design of tooth profiles of non-circular gears with addendum modifications that conform to the given complex transmission ratio curves and based on a series of discrete point sets on the pitch curves, the criteria for tooth profile distortion and undercut in non-circular gears were proposed. With the constraint of no tooth profile distortion and undercut, the addendum modification coefficient was introduced into the calculation of the distorted and undercut segments of the tooth profile of a non-circular gear, and the addendum modification coefficient of each contact point of the non-circular gear was obtained. Based on the generating principle for gear shaping with gear cutters, a theoretical model for calculating the tooth profile of non-circular gears with addendum modification was derived. The cutting and radial feeding motions of the pinion cutter were ignored, and only the meshing motion was considered. The involute tooth profiles of the pinion cutter enveloped the tooth profile of the non-circular gear. 3D automatic non-circular gear model generation software was developed, which was a secondary development product of the software UG. A non-circular gear in a rice potted seedling transplanting mechanism was designed, and the transplanter was developed and tested. The test results showed that the designed tooth profile of non-circular gear achieved the variable transmission ratios required by the transplanting mechanism. When the transplanting efficiencies were 140 plants/min, 160 plants/min and 180 plants/min, the transplanter completed the rice potted seedling transplanting operation with high quality. Keywords: non-circular gear; tooth profile generation; addendum modification coefficient; enveloping characteristics; transplanting mechanism DOI: 10.25165/j.ijabe.20201306.5659 Citation: Zhou M L, Yang Y C, Wei M X, Yin D Q. Method for generating non-circular gear with addendum modification and its application in transplanting mechanism. Int J Agric & Biol Eng, 2020; 13(6): 68–75.